Declines in health literacy and health-related quality of life during the COVID-19 pandemic: a longitudinal study of the Japanese general population - Hirono Ishikawa (BMC, 2021)
Abstract Background During the coronavirus disease 2019 (COVID-19) pandemic, the importance of health literacy (HL) was addressed by public health researchers. We longitudinally examined the changes in general HL and health-related quality of life (HRQOL) between immediately before the COVID-19 outbreak and 1 year later, and how general HL before the outbreak was related to changes in HRQOL in the Japanese general population. Methods Among the Japanese residents aged 20–79 years who participated in our previous study in 2017, 826 were followed-up via self-administered questionnaires in January 2020 and February 2021, for the purposes of this study. The HRQOL was measured using the SF-8, a short version of the SF-36 Health Survey, and general HL was measured using the short form of the European Health Literacy Survey Questionnaire (HL-SF12) in the 2020 and 2021 surveys. Results The physical and mental dimensions of HRQOL as well as general HL declined significantly from immediately before the COVID-19 outbreak to 1 year later (p = .010, p < .001 and p < .001, respectively). The decline in HRQOL, especially the mental dimension, was more significant among women. A lower economic status was also related to a greater decline in HRQOL (p = .026 for the physical dimension and p = .012 for the mental dimension). Higher general HL before the COVID-19 outbreak was associated with a lesser decline in HRQOL in both the physical and mental dimensions (p = .040 and p < .001, respectively) after controlling for possible confounding variables such as gender and economic status. Conclusions Healthcare support is crucial for vulnerable populations during and after the pandemic. General HL may be important for attenuating the decline in HRQOL, by enabling effective use of health information and adaptive behaviors toward health threats. Further studies are needed to better understand the association between HL and HRQOL.